CHEMTAX analysis of phytoplankton assemblages revealed potential indicators for blooms of haptophyte Phaeocystis globosa. (November 2021) - Wang, Jin-Xiu; Kong, Fan-Zhou; Geng, Hui-Xia; Zhang, Qing-Chun; Yuan, Yong-Quan; Yu, Ren-Cheng
Graphical abstract: Highlights: Phytoplankton assemblages in Beibu Gulf are characterized by the CHEMTAX approach. Diatoms, cyanobacteria and haptophytes are major phytoplankton taxa in Beibu Gulf. Bloom-forming Phaeocystis globosa is well represented by 19′-butanoyloxyfucoxanthin. Diatoms are positively associated with P. globosa while cyanobacteria are negative. Temperature and three pigments are potential indicators to predict P. globosa bloom. Abstract: Harmful algal blooms formed by the haptophyte Phaeocystis globosa have been recorded in the Beibu Gulf since 2011. In this study, the composition and variation of phytoplankton assemblages in the Beibu Gulf were studied during an intense bloom of P. globosa from 2016 to 2017, using the CHEMTAX approach. In phytoplankton samples collected from the Beibu Gulf, chlorophyll a (Chl a, 0.046–2.87 μg L −1 ) and fucoxanthin (Fuco, 0.041–13.7 μg L −1 ) were the most abundant pigments. Diatoms were the dominant group of phytoplankton, followed by cyanobacteria (mainly Synechococcus ), haptophytes, cryptophytes, prasinophytes, dinoflagellates, and chlorophytes. Phytoplankton samples were clustered into four communities characterized by diatoms, cyanobacteria, haptophytes containing 19′-butanoyloxyfucoxanthin (the "Hapt-But" subgroup of haptophytes), and haptophytes containing 19'-hexanoyloxyfucoxanthin (the "Hapt-Hex" subgroup of haptophytes). Distribution pattern of the "Hapt-But" subgroup of haptophyte was consistent with that of P. globosa colonies. Diatoms had positive correlation with P. globosa colony abundance, while cyanobacteria had negative correlation. The diagnostic pigments for colony-forming P. globosa (But-fuco), diatoms (Fuco) and cyanobacteria (zeaxanthin), as well as temperature (<20 °C), could serve as potential early-warning indicators for the formation of P. globosa blooms in the Beibu Gulf.